Sustentabilidade ambiental e bancos de desenvolvimento: o caso BNDES - Valente, Cidália de Paula (2016)
The theme "environmental sustainability" has become fundamental in the international agenda, due to the growing socio-economic development process that culminated in increasing demand for the use of natural resources to meet human needs. This growing demand established the concept of sustainable development that reconciles economic growth and environmental conservation. Given the importance of development banks in the process of economic and social development of countries, and the fact that concerns about risks inherent to activities of these actors led to the adoption of responsibility, it is essential to study the role of these banks in relation to environmental sustainability. Thus, the context and the representativeness of BNDES as the main Brazilian development funding instrument led to the purpose of this study, which is to identify as environmental sustainability criteria are adopted in the assessment of credit lines concessions. A single case study of qualitative approach and exploratory nature was conducted, collecting secondary data through extensive literature research, and primary data through desk research and semi-structured interviews (triangulated both in collection and in data analysis). The results showed that the concern with environmental issues in BNDES goes back to the 1970s and 1980s, but it was in the decades of 1990 and 2000, with greater Brazilian participation on the world stage, at events such as the Rio-92 and signing of the Green Protocol, the environmental variable was included in the bank's operations. With the creation of the environmental area, which plays a supporting role to other areas of the bank in project analysis, the environmental issue has gained status within the bank. It was found that the adoption of environmental sustainability criteria emerges from instruments of socio-environmental policy through criteria covering the whole process of evaluation of BNDES’s projects. As well as the socio-environmental policy of the bank, which is a benchmark for all its operations, the criteria are common to all areas. It is noteworthy that the environmental policy of the BNDES, as well as all its actions, are influenced by many different actors, such as the federal government, other financial institutions and large companies, which leads the issue of environmental sustainability beyond the BNDES.